Pengaruh Profitabilitas, Firm Size, Likuiditas Dan Leverage Terhadap Kebijakan Dividen Di Bei - Sumantri, Putu Adhy; Candraningrat, Ica Rika (E-Jurnal Manajemen; Vol 3 No 8 (2014), 2014)
Dividend policy is a financial decision that has been made ??by the company after the company operates and makes a profit. Dividends distributed by companies to investors that the dividend policy is decided by the company. The few things that influence the dividend policy of a company in this study, namely profitability, firm size, liquidity and leverage. The purpose of this study was to determine the significance of the effect of profitability, firm size, liquidity and leverage on dividend policy. This research was conducted at Manufacturing Company in Indonesia Stock Exchange, the number of samples taken 11 companies with a population of 146 companies. The sampling method used was purposive sampling method. Data collected through observation. The analysis technique used is the Multiple Linear Regression. Based on the results of the analysis found that profitability, firm size, liquidity partially significant positive effect on dividend policy. While leverage significant negative effect on dividend policy.